2011
DOI: 10.1158/1541-7786.mcr-11-0097
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Cells Proliferation Is Regulated by Tyrosine Phosphatase SHP1 through c-jun N-Terminal Kinase and Cooperative Induction of RFX-1 and AP-4 Transcription Factors

Abstract: In this study, we show that proliferation of breast cancer cells is suppressed by IGF-1-activated JNK MAPK pathway. The molecular mechanism by which c-jun-NH,-kinase (JNK) activation induces antiproliferative signals in IGF-1-stimulated breast cancer cells remains unknown. Tyrosine phosphatase SHP1 is known to negatively regulate signal transduction pathways activated by cell surface receptors including IGF-1. Moreover, SHP1 transcript and protein levels are increased in epithelial tumors. Therefore, we hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 53 publications
(68 reference statements)
0
26
1
1
Order By: Relevance
“…As a leading type of cancer in women, breast cancer accounts for 25 % of all cases [41]. AP4 has been reported to suppress breast cancer proliferation [17,19]. Low expression of AP4 indicates good prognosis in estrogen receptor-positive breast cancer [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a leading type of cancer in women, breast cancer accounts for 25 % of all cases [41]. AP4 has been reported to suppress breast cancer proliferation [17,19]. Low expression of AP4 indicates good prognosis in estrogen receptor-positive breast cancer [20].…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, AP4 was found to participate in cellular differentiation, cell proliferation [6][7][8][9][10], cell cycle regulation, and apoptosis [11][12][13][14][15][16]. More recent findings show that AP4 is also involved in pathological conditions, for example, AP4 is highly expressed in colon carcinoma, breast cancer, and prostate cancer [15,17,18] and that AP4 suppresses MCF-7 cell proliferation via enhancing the levels of SHP1 and JNK activation [19]. Furthermore, overexpression of AP4 is associated with poor prognosis and lymph node status of ER?…”
Section: Introductionmentioning
confidence: 99%
“…Constitutively phosphorylated PI3K in MDA-MB-231 as well as in R3-MB-231 cells and lack of SSTR3 cytotoxic effect in ER a -negative cells attest the importance of PI3K inhibition in apoptosis. The tyrosine phosphatase PTP-1C is highly expressed in breast tumors (Amin et al, 2011). In MCF-7 and HEK-293 cells, PTP-1C translocation from cytosol to the cell surface is an essential requirement for SSTR mediated apoptosis (War et al, 2011, Srikant andShen, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…proliferation by enhancing SHP1 expression and JNK activation [40]. It indicates that AP4 may play a dual role in cell proliferation via different pathways.…”
mentioning
confidence: 99%